Phylogenetic studies in the South American tribe Dichroplini (Orthoptera: Acrididae: Melanoplinae): is the Paranaense-Pampeano informal genus group a natural clade? - Dinghi, P. A.; Confalonieri, V.; Cigliano, M. M. (Zootaxa, 2009)
The Dichroplini genera Scotussa, Leiotettix, Ronderosia, Atrachelacris, Chlorus, Eurotettix and Dichromatos have been grouped into the “Paranaense-Pampeano” informal genus group, based on characters of the male genitalia. However, recent molecular phylogenetic analyses showed weak support values or no support at all for this group. In this study, we used molecular and morphological characters to test the monophyly of this informal genus group. Morphological characters included aspects of the general morphology, and male and female genitalia as well. Whereas the molecular data was based on one mitochondrial gene: cytochrome oxidase I. Independent and combined phylogenetic analyses of the data were performed under both unweighted and implied weighting parsimony. Our results showed that, when only molecular data is considered, the “Paranaense-Pampeano” informal genus group is not recovered. However, the group is monophyletic according to morphological and combined analyses. The “Paranaense-Pampeano” informal genus group is considered to be a natural clade; therefore, we propose the genus group name Scotussae. As a final remark, the molecular data provided in most cases the same evidence of relationships as morphology.